2023
DOI: 10.1002/est2.447
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of single‐pass solar air heater thermal collector with adding porous media and finned plate

Abstract: The recent study encompasses a practical inspect on adding porous material above absorber flat plate having fins to improve the effectiveness of solar air heater (SAH) collector along with forced air circulation process. The efficiency of the altered model and conventional SAH system is compared at the same time to display the impacts of adding porous material. The model that used porous material is called Model‐2, whereas the conventional SAH is called Model‐1. The measuring data is collected in January 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The Alomar et al 35 method is used to evaluate the indirect uncertainties of the measuring amount which formed as:…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…The Alomar et al 35 method is used to evaluate the indirect uncertainties of the measuring amount which formed as:…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…The results indicate that the efficacy of the novel model surpassed that of the conventional v-corrugated absorber plate. The efficacy of a single-pass solar air heater thermal collector was examined in research conducted by (Alomar et al, 2023), whereby the inclusion of permeable material and an expanded area was investigated. The results indicated that Model 2 had the maximum efficiency level, reaching 67%, while Model 1 obtained an efficiency of 60% at a mass flow rate of 0.02 kg/s.…”
mentioning
confidence: 99%